Solusi Asuransi Syariah (Takaful) dalam Manajemen Risiko Aset Kripto - Luthfiana Basyirah; Nurhayati Nurhayati; Andriyani Samsuri; M. Khoirul Muttaqin (Universitas Proklamasi 45, 2022)
This study aims to analyze Islamic insurance as a solution to crypto asset risk management. This study uses a descriptive approach, namely research that tries to describe and explain the data obtained with secondary data. This study uses a type of literature study research, namely the source of data obtained from literature studies and various kinds of literature in accordance with the theme of the discussion. The results of this study indicate that: first, the risks that occur in assets due to technology failure, system damage, hacking, loss of capital, fraud, malpractice, war risk, natural disasters, death, bankruptcy, sanctions, and non-compliance are included in the subjective risk classification. , objective and pure. Second, Islamic insurance schemes (takaful) are essential to be included in cryptocurrency risk management in order to increase public confidence in the market. The implications of this article can be considered for cryptocurrency transactions in accordance with Islamic sharia because the risks that will occur in crypto assets have been mitigated by the existence of a sharia insurance scheme (takaful).